2016
DOI: 10.1016/j.joa.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Lead extractions in patients with cardiac implantable electronic device infections: Single center experience

Abstract: BackgroundLead extraction using laser sheaths is performed mainly for cardiac implantable electronic device (CIED) infections. However, there are few reports concerning the management of CIED infections in Japan.Methods and resultsLead extraction procedures were performed in 183 patients targeting 450 leads (atrial leads: 170, ventricular: 181, implantable cardioverter-defibrillators (ICDs): 79, and coronary sinus: 20). One hundred twenty patients (65.6%) presented with pocket infections without the presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
1
20
1
Order By: Relevance
“…Therefore, it is important to know the prognosis of transvenous lead extractions as well as its influencing factors. Studies of lead extraction in Japanese patients have been reported . However, the prognosis after transvenous lead extraction in Japanese patients, especially those with lead‐related infective endocarditis, has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to know the prognosis of transvenous lead extractions as well as its influencing factors. Studies of lead extraction in Japanese patients have been reported . However, the prognosis after transvenous lead extraction in Japanese patients, especially those with lead‐related infective endocarditis, has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…However, data on microbiology of CIED infection in Asian countries are limited. Studies from Japan and China showed that Staphylococcus remained the predominant pathogen associated with CIED infection …”
Section: Introductionmentioning
confidence: 99%
“…Studies from Japan and China showed that Staphylococcus remained the predominant pathogen associated with CIED infection. [26][27][28] In Thailand, CIED implantation has been increasingly performed.…”
Section: Introductionmentioning
confidence: 99%
“…While the relapse rate due to infection is 0% to 4.2%, when a complete removal is performed, this rate increases to 50% to 100% in a partial extraction (1, 35). …”
mentioning
confidence: 99%